Accounting an International Perspective - GERNON, Helen (McGraw-Hill Book Company, 2001)
An introductory or intermediate accounting supplement. This paper bound text is designed to supplement introductory accounting texts with additional mini-cases and readings covering international accounting concepts. The book provides a general, non-technical overview of international accounting and covers both financial and managerial accounting topics